Effect of adding arginine at different concentrations to experimental orthodontic resins: an in vitro study - Ana Lídia Correa SANTOS; Lourenço CORRER-SOBRINHO; Fernanda Midori TSUZUKI; Anália Gabriela FACURY FERRAZ; José Guilherme NEVES; Mário Alexandre Coelho SINHORETI; Eduardo Martinelli FRANCO; Ana Rosa COSTA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to assess the effect of adding arginine at different concentrations to commercial and experimental orthodontic resins on shear bond strength (SBS), as well as on the antimicrobial activity of arginine against S. mutans. Metal brackets were bonded onto the surface of 120 bovine incisors using Transbond, OrthoCem, and an experimental resin (ER), adding 0, 2.5, 5, and 7 wt.% of arginine. The SBS test was performed in deionized water at 37 ºC for 24 h, at 0.5 mm/min. SBS test results were subjected to two-way ANOVA and Tukey's test (α = 0.05). CFU/mL data (antimicrobial assessment) were assessed by Kruskal-Wallis and Dunn's tests (α = 0.05). No statistical difference between the resins was observed in untreated groups (p > 0.05). The addition of arginine at 2.5% (27.7 MPa) and 5% (29.0 MPa) increased the SBS of Transbond when compared (p < 0.05) to OrthoCem (18.5 and 15.6 MPa, respectively) and ER (16.3 and 18.1 MPa, respectively). Arginine at 7% improved the SBS of Transbond (24.1 MPa) and ER (21.0 MPa), which was statistically higher (p < 0.05) than OrthoCem (12.6 MPa). OrthoCem did not show a statistically significant difference at the three concentrations of arginine (p > 0.05). The addition of arginine to resins reduced the count of S. mutans (p < 0.05). As for ER, all concentrations of arginine significantly decreased CFU/mL (p < 0.05). Among commercial resins, only 7% of arginine significantly reduced CFU/mL. The addition of arginine did not interfere with the bond strength and demonstrated antibacterial activity against S. mutans.